Influenza vaccination among Malaysian healthcare workers: a survey of coverage and attitudes - Shuaibu, Hudu Abdullahi; Mohammed Harmal, Nabil Saad; Osman, Malina; Sekawi, Zamberi (Malaysian Medical Association, 2016)
Background: Healthcare workers (HCWs) are at increased risk of getting influenza than the general population, therefore putting patients at risk of nosocomial infection. Influenza vaccination coverage among HCWs is low despite the availability of a safe and effective vaccine. However, the reasons for such a poor uptake are not well reported in Malaysia. This study aimed at assessing the rate of influenza vaccination uptake, knowledge and attitude of healthcare workers regarding influenza, and employers’ policy on influenza vaccination. Methods: A cross-sectional questionnaire survey was conducted in three hospitals in the Klang Valley. Mann–Whitney test was used to assess possible differences in knowledge and attitude towards flu vaccination and the χ 2 was used for categorical variables. Analyses were performed with SPSS 22.0. Results: A total of 690 questionnaires were distributed; 527 were returned (giving a response rate of 76.4%. The vaccine uptake was 51.4% with the majority (83.5%) of those believing they were vaccinated to protect themselves. Higher proportion of vaccinated HCWs (p <0.05) agreeing to the fact that influenza is a serious threat to their health, however, 10% were not sure of its safety. Eighty-three (15.7%) claimed their employers did not have a vaccination policy, while 43.3% were not sure if their employers have vaccination policy. Conclusion: This study has demonstrated more than half of the healthcare workers were vaccinated, with a significant proportion of the healthcare workers believed they were vaccinated to protect themselves, while most of those that were not vaccinated claimed they are worried about the safety of the vaccine. Most employers did not have a flu vaccination policy in place. Hence, the need for government to enforce such policy and make annual flu vaccination free and compulsory for all healthcare workers.